Immunogenicity and safety of reduced-antigen tetanus, diphtheria and acellular pertussis vaccination in adults treated for obstructive airway diseases. Issue 1 (31st December 2023) - Van den Steen, Peter; Cheuvart, Brigitte; Deraedt, Quentin; Valdes Verelst, Laura; Shamarina, Dasha
ABSTRACT: Patients with obstructive airway diseases (OAD), like chronic obstructive pulmonary disease (COPD) and asthma, may be at increased risk of pertussis infection. Pertussis may also trigger COPD and asthma exacerbations. Vaccination against pertussis could help protect OAD patients from the additional burden of pertussis, but there may be hesitancy related to vaccine safety and immunogenicity in such patients. We performed a meta-analysis on 5 clinical trials in adults receiving reduced-antigen tetanus-diphtheria-acellular pertussis vaccine (Tdap, Boostrix, GSK), from which we selected participants on active OAD treatment. We compared immunogenicity and reactogenicity outcomes of the meta-analysis with data from the overall populations of Tdap-vaccinated adults from 6 Tdap trials (including the 5 in the meta-analysis). The meta-analysis comprised 222 adults on active standard OAD treatment. One month post-Tdap, 89.0% and 97.2% of these adults, respectively, achieved seroprotective anti-diphtheria and anti-tetanus antibody concentrations; 78.3%–96.1% showed booster responses across the 3 pertussis antigens. These rates were consistent with those in the comparator population. The most frequently reported solicited local and systemic adverse events within 4 days post-Tdap were injection site pain (47.7%) and fatigue (19.3%), with low rates of grade 3 intensity (0.9% and 2.8%). This was consistent with Tdap reactogenicity in the comparator population. Evaluation of unsolicited and serious adverse events within 1 month post-Tdap did not identify safety concerns. In conclusion, Tdap was immunogenic and well tolerated in adults under active standard OAD treatment, with immunogenicity and safety profiles consistent with those in a comparator population representing the general adult population. Plain Language Summary: Whooping cough is a very contagious respiratory disease that is most dangerous for young babies but can affect people of all ages. People with chronic lung diseases like asthma or chronic obstructive pulmonary disease (COPD) may be more likely to get ill and suffer from complications from whooping cough. Vaccination against whooping cough is an important way to help protect these people. However, some doctors may hesitate to vaccinate patients because they may worry that vaccination could worsen asthma or COPD symptoms or that drugs taken by these patients could make vaccines work less well. We therefore looked at the immunogenicity and safety of a whooping cough vaccine ( Boostrix, GSK) in adults treated for chronic lung diseases like asthma or COPD. We analyzed data from 5 previous clinical studies and specifically selected data from patients taking standard medication for chronic lung diseases in these studies. We found that the immune response to whooping cough vaccination in these patients was comparable to that in a comparator group representative of the general adult population receiving Boostrix . The vaccine was as well tolerated in patients with chronic lung diseases as in the general adult population. Our results suggest that the whooping cough vaccine Boostrix can be safely given to adults taking standard medication for chronic lung diseases to help prevent severe illness and complications from whooping cough.